2006
DOI: 10.1111/j.1745-4565.2005.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIBIOTIC RESISTANCE OF CAMPYLOLOBACTER ISOLATED FROM AUTOMATED BROILER FARMS

Abstract: The use of the same antibiotics in animal food and conventional medicine can cause problems in the treatment of human diseases, because poultry frequently carry human pathogens. The aim of the present study was to determine the antibiotic resistances patterns of Campylobacter jejuni isolated from the rearing environment of broiler chickens – litter, drinking water, feed and the bird's cloaca. The results showed significant resistance to the following antibiotics: sulfonamide (77%), tetracycline (100%), erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…5 In contrast, ciprofloxacin resistance has been reported in the USA (19%) 12 and a range of European nations (14.9% of C. jejuni and 39.6% of C. coli isolates). 11 An absence or near absence of ciprofloxacin resistance has also been reported from Brazil, 16 Canada 15 and Norway. 17 In contrast to our findings, other studies have reported that C. coli isolates show higher levels of resistance than C. jejuni isolates.…”
Section: Discussionmentioning
confidence: 93%
“…5 In contrast, ciprofloxacin resistance has been reported in the USA (19%) 12 and a range of European nations (14.9% of C. jejuni and 39.6% of C. coli isolates). 11 An absence or near absence of ciprofloxacin resistance has also been reported from Brazil, 16 Canada 15 and Norway. 17 In contrast to our findings, other studies have reported that C. coli isolates show higher levels of resistance than C. jejuni isolates.…”
Section: Discussionmentioning
confidence: 93%
“…in poultry and its importance in human disease, studies regarding the resistance profile within this genus are not common, which could be explained by the difficulty of cultivating, isolating, and maintaining these bacteria in the laboratory. However, some previous data pointed to high resistance frequencies [70,71]. The data available in the last decade demonstrate the maintenance of these profiles.…”
Section: Campylobacter Sppmentioning
confidence: 89%
“…Similar results were found in the federal district (MW), with 16 Campylobacter jejuni strains isolated from chicken carcasses with high resistance to ciprofloxacin (100%), nalidixic acid, streptomycin, tetracycline, gentamycin (94% each), and chloramphenicol (38%), and in Parana State (S) in a study with C. jejuni, C. coli, and C. lari with detection of 75% of MDR strains, and high frequencies of resistance (>70%) to cephalothin, nalidixic acid, ciprofloxacin, and tetracycline [64,70].…”
Section: Campylobacter Sppmentioning
confidence: 99%